Effects of zinc and multimineral vitamin supplementation on glycemic and lipid control in adult diabetes - Priyanka Gunasekara (Dove Medical Press, 2011)
Priyanka Gunasekara1, Manjula Hettiarachchi2, Chandrani Liyanage2, Sarath Lekamwasam21Coronary Care Unit, Teaching Hospital, Karapitiya, Galle, Sri Lanka; 2Faculty of Medicine, University of Ruhuna, Galle, Sri LankaAims: To evaluate the effects of zinc with or without other antioxidants on blood glucose, lipid profile, and serum creatinine in adult diabetics on long-term follow-up.Materials and methods: Patients (n = 96) were randomly allocated to three groups: group A (n = 29) was supplemented with oral zinc sulfate (22 mg/day) and multivitamin/mineral (zinc+MVM) preparation; group B (n = 31) was given the same preparation without zinc (MVM); and group C (n = 36) was given a matching placebo for a period of 4 months in a single-blinded study. Blood samples were taken at baseline and after 4 months of supplementation to assess blood glucose (fasting and postprandial) and glycosylated hemoglobin (HbA1C%) and serum levels of zinc, creatinine, and lipids.Results: The zinc+MVM group had a mean change of fasting blood sugar -0.33 mmol/L (standard error of the mean 0.21 mmol/L) and was significant (P = 0.05) when compared with the other two groups (mean change in the MVM group +0.19 (0.31) mmol/L and +0.43 (0.23) mmol/L in the control group, respectively). The HbA1C% level reduced significantly, irrespective of the baseline level, in zinc+MVM-supplemented individuals. In the other two groups, the change of HbA1C% level was not significant. Serum lipid levels reduced significantly in the zinc+MVM and MVM groups.Conclusions: Zinc+MVM supplementation showed beneficial effects in the metabolic control of adult diabetics in addition to elevating their serum zinc level. Zinc supplementation improved glycemic control measured by HbA1C% and fasting and postprandial glucose. Furthermore, zinc supplementation lowered serum cholesterol and cholesterol/high-density lipoprotein ratio.Keywords: zinc, multivitamin mineral supplementation, diabetes, glycemic control